Effect of Silicon dioxide coating of acrylic resin surfaces on Candida albicans adhesion - SILVA,Rossano Vinícius Dala Rosa (2020)
Abstract Acrylic resin has been used in the manufacture of prostheses, however, in the oral cavity, this material starts to retain microorganisms capable of causing gingival inflammation due its porosities. The aim of this study was to evaluate the influence of the use of silicon dioxide as a coating layer applied onto acrylic resin, on the adhesion of Candida albicans (Ca). After the incubation period in Sabouraud Dextrose Broth, a total of 1 ml of the Ca suspension was added to plate wells, each well containing a specimen of acrylic resin. The adhesion ability of Ca on acrylic resin was determined by counting colonies. Three groups (n = 6) of acrylic resin were assessed: with polishing (RP); without polishing (RW); with polishing and coating layer of silicon dioxide (RPC). Ca deposited on the surface of the acrylic resin was also observed using Scanning Electron Microscopy (SEM). Statistical assessment by Kruskal-Wallis and Student-Newman-Keuls Method were done (α = 2%). There was significant difference among the groups. The RPC group showed the lowest growth, with an average of 5.59 Log CFU/cm 2 ; there was a statistically significant difference in relation to group RW, which presented a growth of 6.07 Log CFU/cm 2 and to group RP with 5.91 Log CFU/cm 2 (p < 000.1). SEM images demonstrated that in the RP and RPC group, the surface of the resin had greater regularity, and smaller number of microorganisms. The application of silicon dioxide coating on acrylic resin appears to be a promising alternative, and its use can help in reducing the adhesion of Ca in prostheses.